Differential Methylation of Syncytin-1 and 2 Distinguishes Fetal Growth Restriction from Physiologic Small for Gestational Age - Makaroun, Sami P.; Himes, Katherine P. (American Journal of Perinatology Reports, 2018)
Objective The retroviral genes encoding Syncytin-1 (SYN1) and Syncytin-2 (SYN2) are epigenetically regulated, uniquely expressed in the placenta and critical to placental function. We sought to determine if placental expression and methylation patterns of SYN1 and SYN2 from pregnancies complicated by fetal growth restriction (FGR) differed from physiologic small for gestational age (SGA) and appropriate for gestational age (AGA) controls.Study Design Placental biopsies were obtained from AGA, SGA and FGR neonates delivered at >36 weeks gestation. SGA and FGR were defined as birth weight <10% with FGR additionally requiring abnormal fetal testing. We quantified DNA methylation of SYN1 and SYN2 by EpiTyper and gene expression by RT-qPCR.Results We identified 10 AGA, 9 SGA and 7 FGR placentas. There was decreased methylation in SYN1 and SYN2 in FGR relative to AGA and SGA. When the sum of SYN1 and SYN2 methylation was used for prediction of FGR from SGA, the area under the receiver operator characteristic curve was 0.9048 (0.7602, 1).Conclusion SYN1 and SYN2 methylation marks differ in FGR and SGA. We plan future studies to examine these markers in cell free DNA to determine if these methylation changes could be used as a biomarker for FGR.
Keywords: retroelements; syncytin; methylation; placenta; fetal growth restriction; intrauterine growth restriction